Figuralidades: da tradução ao poético na fotografia de arte contemporânea - Isabel Florencio Braga (2009)
This thesis analyses the photography of contemporary art from the 1970s to nowadays and aims to understand the interfaces between art photography and literature using the intermidiality studies as theoretical reference. Seeking to understand how certain aspects of literary discourse migrate to photography and create new forms of figuration, the analysis of this work is organized in four main aspects: translation, narrative, fictionalization, and defiguration. These categories allow the understanding of how the photography discourse detached from the description forms to provide a figural poetic discourse. From a text thatdeals with the description in narrative discourse, the photography discourse is free of figurative forms and could create new ways of transgression for - in the last moment achieve the dilution of the descriptive layer and construct a discourse marked by the defiguration.